New U-Pb age constraints on the geological history of the Ganderian Bras d'Or terrane, Cape Breton Island, Nova Scotia - van Rooyen, Deanne; Barr, Sandra M.; White, Chris E; Hamilton, Michael A. (NRC Research Press (a division of Canadian Science Publishing), 2019)
The northern Appalachian orogen preserves evidence of a complex history of amalgamation of terranes with both Laurentian and Gondwanan affinities. The Ganderian Bras d'Or terrane of central Cape Breton Island is not well-represented elsewhere in the orogen and its relationship to other Ganderian terranes is enigmatic, particularly with respect to its pre-Neoproterozoic history. The Boisdale Hills and Kellys Mountain areas contain the oldest metamorphic rocks in the Bras dâ Or terrane. Quartzite units in the Boisdale Hills have detrital zircon populations with ages ranging from 3.2 Ga to ca. 1 Ga. Paragneiss units from the Kellys Mountain area contain Meso- to Neoproterozoic detrital zircons, in which the youngest grains indicate that the maximum depositional age is The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.